Analysis of Utilization of Liquid Smoke from Agroindustry Waste (Coconut Sheels, Palm Oil Bunches, and Palm Shells) - Fahlin, Dhisti Khairunnisa; Lenggo Geni Katlin Jambak (Journal of Engineering Science and Technology Management (JES-TM), 2025)
The increasing production of oil palm and coconut commodities has intensified environmental challenges associated with agro-industrial solid waste, particularly coconut shells, oil palm fruit bunches, and palm shells. This study aims to analyse the utilization of liquid smoke derived from these agro-industrial wastes and to evaluate their potential applications based on previous research findings. The study was conducted using a descriptive–analytical literature review, in which relevant scientific articles were systematically selected and analysed according to raw material type, pyrolysis process, chemical characteristics, and application of liquid smoke. The results indicate that liquid smoke derived from coconut shells generally exhibits higher phenolic content, making it suitable for antimicrobial, antifungal, and medicinal applications, while liquid smoke from oil palm residues shows strong potential as an organic pesticide, fungal control agent, and natural rubber coagulant due to its organic acid content. These findings demonstrate that agro-industrial waste can be effectively vaporized into value-added products through liquid smoke production, contributing to waste reduction and environmental sustainability. This study provides a comparative framework for selecting appropriate biomass sources for specific liquid smoke applications and supports the development of sustainable waste management strategies.